2007
DOI: 10.1111/j.1365-2109.2007.01706.x
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid composition of edible parts of three-year-old experimental scaly crossbreds of common carp (Cyprinus carpio, Linnaeus 1758)

Abstract: The aim of this study was to compare the amino acid (AA) composition of edible parts of three experimental groups of carp, i.e. a pure line of Pr› erov scaly carp (PS), a hybrid line of Pr› erov scaly carp and Northern mirror carp (PS Â M72), and a hybrid line of Pr› erov scaly carp and Ropsha scaly carp (PS Â ROP), with the quality of the edible parts of control hybrids of Hungarian and Northern mirror carp (M2 Â M72) in harvest size (K 3 ). A comparison between the controls (M2 Â M72) and experimental carp (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“…No statistically significant effects of cyanobacterial water bloom on the content of amino acids in muscles were found in the common carp, because the variation in amino acids in experimental fish and controls was similar. The results are comparable with those published by Buchtová et al (2007).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…No statistically significant effects of cyanobacterial water bloom on the content of amino acids in muscles were found in the common carp, because the variation in amino acids in experimental fish and controls was similar. The results are comparable with those published by Buchtová et al (2007).…”
Section: Resultssupporting
confidence: 91%
“…Fish are considered to be food of high dietetic value owing to their characteristic composition of amino acids (AA), fatty acids (FA), vitamins and easy digestibility (Steffens 1997; Murray & Burt 2001; Buchtová, Svobodová, Kocour & Velíšek 2007). The composition of fish muscles is considerably influenced by many biotic and abiotic factors such as fish species, age, gender, breeding technology, environmental conditions, nutrition, stress and others (Henderson & Tocher 1987; Fajmonová, Zelenka, Komprda, Kladroba & Sarmanová 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The contents of fat encountered in the meat of other fi sh va riants were lower than what was measured at the test beginning, but the fi gures lacked statistical signifi cance. The spectrum of fatty acids present in the fi sh muscle at the experiment's beginning did not fully correspond to what was observed in carps living in ponds and fed by cereals as described by Csengeri and Farkas (1993), Steff ens and Wirth (2007), Kmínková et al (2001), Fajmonová et al (2003), Buchtová et al (2007), Steff ens and Wirth (2007) and Vácha et al (2007).…”
Section: Resultsmentioning
confidence: 64%
“…The authors also reported an insignifi cant eff ect of the sex on the chemical composition and the spectrum of FA in the carp meat. In common carp the composition of fatty acids in the fat is not substantially infl uenced by its sex or the kind of hybrid (Buchtová et al, 2007). Fauconneau et al (1995) describe twice or three times greater activity of enzymes synthesizing the fatty acids in cyprinoids bred in water 2 °C to 10 °C than in fi sh living in water 20 °C to 30 °C.…”
mentioning
confidence: 99%
“…The study is a part of a comprehensive assessment of the tested carp hybrids, and it complements papers published by Buchtová et al (2006ab) and (Buchtová et al 2007). …”
mentioning
confidence: 69%